TEACHER'S CORPORAL PUNISHMENT TO STUDENTS AS LEARNING COMMUNICATION AT MAMBAUL HISAN CHILDREN'S ISLAMIC BOARDING SCHOOL PONOROGO - Choiroh, Himatul; Marwantika, Asna Istya (QAULAN: Journal of Islamic Communication, 2021)
Learning communication is the process of delivering messages from teachers to students. One of the objectives of learning communication is to form a student's disciplinary attitude. The application of discipline sometimes requires corporal punishment as done in Mambaul Hisan Children’s Islamic Boarding School Ponorogo. The purpose of this research is to describe the form of corporal punishment of teachers in learning communication at Mambaul Hisan Children’s Islamic Boarding School Ponorogo. This research was conducted using descriptive research method with qualitative approach. Data collection techniques in this research are observations, interviews and documentation. Data analysis techniques using George Herbert Mead's symbolic interactionalism theory. The result of this study is the first, the application of corporal punishment in learning communication in Mambaul Hisan in the form of verbal and non verbal communication. Verbal communication is done by the teacher by warning students who make mistakes, nonverbal communication by giving corporal punishment such as being pinched, beaten, or tweaked. Second, the implication of corporal punishment given by teachers to students is a deterrent attitude and so as not repeating their mistakes.